2022
DOI: 10.1186/s12885-022-09695-x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal/genitourinary perforation and fistula formation with or without bevacizumab in patients with previously irradiated recurrent cervical cancer: a Korean multicenter retrospective study of the Gynecologic Oncology Research Investigators Collaboration (GORILLA) group (GORILLA-1001)

Abstract: Background This study aims to evaluate the incidence of and identify risk factors for gastrointestinal (GI) and genitourinary (GU) fistula or perforation formation with or without bevacizumab in patients with recurrent cervical cancer who underwent pelvic radiation therapy (RT). Methods Medical records of patients with recurrent cervical cancer who previously underwent pelvic RT between 2007 and 2020 were retrospectively reviewed. Clinicopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Other studies that had examined such overall survival outcomes included only small numbers of patients—24 and 7 patients, respectively, thus highlighting the importance of the current study [ 9 , 10 ]. Other such studies examined perforation and fistula formation together and included only a small number of patients with a perforation ( n < 10) [ 20 ]. Similarly, although the large database study from Wichelmann and others included 1375 patients with gastrointestinal perforation, these investigators reported only death rates, not overall survival and not whether surgery was undertaken [ 8 ].Thus, the overall survival data reported here provide a contemporary experience that enables patients, their families, and their healthcare providers to make better-informed management decisions and better informed expectations after the occurrence of this devastating drug-induced complication.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that had examined such overall survival outcomes included only small numbers of patients—24 and 7 patients, respectively, thus highlighting the importance of the current study [ 9 , 10 ]. Other such studies examined perforation and fistula formation together and included only a small number of patients with a perforation ( n < 10) [ 20 ]. Similarly, although the large database study from Wichelmann and others included 1375 patients with gastrointestinal perforation, these investigators reported only death rates, not overall survival and not whether surgery was undertaken [ 8 ].Thus, the overall survival data reported here provide a contemporary experience that enables patients, their families, and their healthcare providers to make better-informed management decisions and better informed expectations after the occurrence of this devastating drug-induced complication.…”
Section: Discussionmentioning
confidence: 99%